CHARACTERISTICS OF KINDEGARTEN STUDENTS’ PERFORMANCE ON MORPHOLOGICAL AWARENESS - Nur Karunia; Eri Kurniawan (Universitas Pendidikan Indonesia, 2019)
The purpose of this study is to describe the characteristic of high-performing and low-performing students based on the morphological awareness test. This research is about the morphological awareness of 5-6-year-old kindergarten students in Bandung. The method used is the descriptive quantitative method, using questionnaires and interview as the data collection instruments. The instruments were given to the parents of 12 kindergarten children who showed high-performance and low-performance. The results showed that the characteristics of high-performing students is that they were from higher SES families (better education, job, and income), and they use Bahasa Indonesia dominantly.